The Capability of Cinnamon as an Off-Flavor Masking Agent for Spirulina platensis enriched Food Product - Wahdan Fitriya; Khusnul Alfionita (Jurnal Perikanan Universitas Gadjah Mada, 2018)
The purpose of this research was to know the effectiveness and the description of aroma of cookies, flakes, and dried noodles fortified with biomass of Spirulina platensis microalgae and cinnamon powder. Fortification was done to increase the nutritional value while the addition of cinnamon powder was done as an aroma masking ingredient to reduce off-flavor of the product. The observations included hedonic test using 60 panelists to find out the best concentration of cinnamon powder additions favored by panelists, followed by quantitative descriptive analysis (QDA) using trained panelists to know the aroma description of the product. The cinnamon powder added to each product was 2.5; 5; 7.5; and 10%. The results showed the concentration of cinnamon for cookies, flakes, and spirulina drieds noodles were 10; 2.5; and 2.5 %, respectively. The selected product was then tested by QDA and generated respectively 13; 12; and 10 perceptions of aroma, while dominant perceptions emerging were cinnamon-like, sunflower seed-like, sand ginger-like, and caramel-like.